Desarrollo de un modelo de gestión basado en pilares de World Class Manufacturing para un Laboratorio de Procesos Industriales. Caso de Estudio: Escuela Colombiana de Ingeniería Julio Garavito (2020)
The laboratories and workshops of industrial processes of the Institutions of Higher Education IES seek to be at the forefront in terms of technology, facilities, personnel, processes and maintenance. This implies that they must carry out appropriate management work, since a modern space without an administrative model according to demand, could be seen as a series of efforts and unjustified and lost investments. The lack of orientation of the service towards the client, the disorder and the constant presence of waste, the lack of flexibility in operations and the disintegration of services, contribute to reducing the competitiveness and productivity of laboratories according to Poor, Kocisko, and Krhel (2016). The industrial processes laboratory of this case study seeks to increase its competitiveness by developing a tool that contributes to successfully managing its operation, in accordance with the experiences expressed by management and its users. This work is carried out through an adaptation of the development phase of the concept of Ulrich's methodology (2009), where through the application of interviews and surveys to the stakeholders of the laboratory, their main needs are determined and they identify and they define the processes that are developed there to later be included in the adaptation and development of the model based on World Class Manufacturing WCM pillars. The maintenance of machinery, equipment and tools is the most pressing need in the machining and lathe processes, which are carried out more than once a week for the normal execution of the academic activities in the IES.